More is Better: The Association of Multiple Experiential Learning Courses and Graduation Rate Among College Students. - Swayze, Anita Carol; Rost, Jim; McCormick, Janet (Experiential Learning and Teaching in Higher Education, 2025)
As federal and state governments have prioritized a college completion agenda, there is an increased emphasis on graduation rates as a key measure of student success. Rising tuition costs and skepticism about the return on investment in higher education have driven initiatives like the Complete College agenda and evolving funding formulas. As such, colleges and universities have implemented Quality Enhancement Plans (QEPS) to better support their students and improve student success outcomes. Prior research has demonstrated that student participation in Experiential Learning (EXL) as a foundational QEP has had a significant positive effect on student success in higher education. Building on prior research, this article examines whether graduation frequency at a large regional institution in Tennessee increases incrementally with each experiential learning course completed. Results of this study indicated that there was a significant association between graduation frequency and incremental completion of EXL courses.